The Relationship between High-reliability practice and Hospital-acquired conditions among the Solutions for Patient Safety Collaborative. Issue 5 (24th September 2021) - Randall, Kelly H.; Slovensky, Donna; Weech-Maldonado, Robert; Sharek, Paul
Abstract : Introduction: Theoretically, the application of reliability principles in healthcare can improve patient safety outcomes by informing process design. As preventable harm continues to be a widespread concern in healthcare, evaluating the association between integrating high-reliability practices and patient harms will inform a patient safety strategy across the healthcare landscape. This study evaluated the association between high-reliability practices and hospital-acquired conditions. Methods: Twenty-five pediatric organizations participating in the Children's Hospitals Solutions for patient safety collaborative participated in this nonexperimental design study. A survey utilizing the high-reliability healthcare maturity model assessed the extent of implementing high-reliability practices at each participating site. We analyzed responses for each component and a composite score of high reliability against an aggregate measure of hospital-acquired conditions. Results: Of the 95 invited sites, 49 responded and 25 were included in the final results. There was a significant inverse relationship between the culture of safety component score and the Serious Harm Index (odds ratio [OR] = 0.63, 95% confidence interval [CI] 0.42–0.95, P = 0.03). There was no association between the overall high-reliability score (OR = 0.91, 95% CI 0.78–1.05, P = 0.19), the Leadership component score (OR = 0.97, 95% CI 0.70–1.33, P = 0.84), or the robust process improvement (RPI) component score (OR = 0.75, 95% CI 0.41–1.28, P = 0.26) and the Serious Harm Index. Conclusion: The integration of high-reliability principles within healthcare may support improved patient safety in the hospital setting. Further research is needed to articulate the breadth and magnitude of the impact of integrating high-reliability principles into healthcare.